The Six-Minute Walk Test on the Treadmill - Prochaczek, Fryderyk; Brandt, Jacek S.; Żmuda, Witold; Świda, Katarzyna R.; Szczurek, Zbigniew W.; Gałecka, Jerzy; Winiarska, Agnieszka (IntechOpen, 2012)
None